Are Known Lung Dose Limits Valid for all Patients? (Global Journal of Medical Research, 2023)
Radiotherapy is one of the pillars of the treatment of lung cancer and it can be used as an ablative therapy alone in the early stages of the disease or combined with chemotherapy in more advanced stages 1 Despite its curative role in many settings radiotherapy is not without side effects One of the most unwanted side effects is radiation pneumonitis RP RP is an inflammatory response resulting from damage to the irradiated lung parenchyma 2 that typically occurs within six months of treatment completion 3 Several factors appear to be associated with the risk of developing RP and its severity including patient-related tumor-related and treatment-related dosimetric factors as well as tumor size and location 4 Patients receiving chemoradiotherapy or with prior lung resection are also in the group of patients at high risk of developing RP 5-6 However the analysis of all these variables in the calculating toxicity potentials is uncommonly performed due to the lack of suitable algorithms